Factors Influencing Innovative Activities in Selected Enterprises - Kwasniewski, Jacek Piotr (American Journal of Management, 2025)
The article aims to analyze the factors influencing innovative activities in construction companies in Wielkopolska. As a key strategic element, innovation plays an important role in ensuring competitiveness in a dynamically developing market environment. The research was conducted on a sample of 80 companies and 5136 employees, focusing on financial outlays on innovation, technological advancement and modern material techniques. In particular, attention was paid to the relationships between these factors, the inclination to undertake innovative activities, and the influence of sociodemographic variables (gender, age, education) on the approach to innovation. The statistical analysis results showed significant correlations, confirming the importance of appropriate investments and technological resources in stimulating innovative activity. The research that was conducted emphasizes the need for further monitoring of innovation factors and adapting companies’ strategies to the changing market and technological context, which can contribute to the sustainable development of the construction sector in Poland.